Formulation of Mesoporous Silica Nanoparticles for Controlled Release of Antimicrobials for Stone Preventive Conservation - Presentato, Alessandro; Armetta, Francesco; Spinella, Alberto; Chillura Martino, Delia Francesca; Alduina, Rosa; Saladino, Maria Luisa (Frontiers in Chemistry, 2020)
The biotic deterioration of artifacts of archaeological and artistic interest mostly relies on the action of microorganisms capable of thriving under the most disparate environmental conditions. Thus, to attenuate biodeterioration phenomena, biocides can be used by the restorers to prevent or slow down the microbial growth. However, several factors, i.e. biocide half-life, their wash-out because of environmental conditions, and their limited time of action make necessary their application repeatedly, leading to negative economic implications. Sound and successful treatments are represented by controlled release systems (CRSs) based on porous materials, where mesoporous silica ones have attracted burgeoning attention thanks to their peculiar physicochemical features, including high surface area, high surface-to-volume ratio, spatial confinement, tunable pore, and particle size, as well as their easy surface functionalization. Here, we report on the design and development of a CRS system based on mesoporous silica nanoparticles (MSNs), as a carrier, which was loaded with a commercially available biocide. MSNs were prepared by the sol-gel method assisted by oil in water emulsion and characterized by X-ray diffraction, Infrared and NMR Spectroscopy, and Transmission Electron Microscopy. Biocide loading and its release were carried out in the water and monitored by UV-Vis Spectroscopy and microbiological assay. Beside, this innovative formulation was useful in inhibiting the in vitro growth of Kocuria rhizophila, an environmental Gram-positive bacterial strain, as well as in the case of biomass contaminating a real case study (i.e., stone derived from the Santa Margherita cave located in Sicily, Italy), after several months of treatment thus opening for innovative treatments of deteriorated stone artefacts.